Protein-solvent interaction and simulation studies of solvent stable and thermostable lipase from Bacillus strain 42 in water-solvent mixtures - Tengku Abdul Hamid, Tengku Haziyamin; Mohd Latif, Muhammad Aliff; Raja Abd Rahman, Raja Noor Zaliha; Basri, Mahiran; Salleh, Abu Bakar (2008)

(untitled)
A purified solvent stable and thermostable recombinant lipase, Lip 42, isolated from Bacillus sp. strain 42 was previously shown to be stable in polar organic solvents such as dimethyl sulfoxide (DMSO) and methanol. Stabilities in different solvent compositions were studied based on 40˚C pre-incubation in solvent and the purified lipase was shown to retain at least 100% residual activity in up to 45% v/v DMSO and 45% v/v methanol. In 60% v/v DMSO, 68% of residual activity was retained, however, this dramatically reduced to 6.5 % at 65% v/v DMSO. Activity enhancement was recorded at lower solvent composition (less than 45% v/v solvent), whereby, at 30% v/v DMSO, enhancement was recorded to be as much as 35%. Enhancement tends to increase as temperature increases. Based on these solvent stability margin, molecular dynamic simulations were then carried out in the presence of water, 60% v/v DMSO + 40% v/v water and 100% v/v DMSO, by using a structure model predicted from a highly homologous (97%) lipase (PDB:1JI3). Results showed that the Lip 42 structure was retained and the flexibility of polypeptide backbone decreased or increased depending on the location of loop regions. Flexibility changes in the helixloop-helix-motif covering catalytic triad were found to be associated with a hydrophobic cluster region. The presence of 60% v/v DMSO resulted in the disorganization of the cluster, accompanied with non-native H-bonds formations. However, the cluster still presents in 100% v/v DMSO and resembles to that of water simulation. Mutant form of lip 42 V174S contains residue substitution near the cluster and within helix-loop helix motif. At 50˚C pre-incubation, the mutant lost as much of high temperature enhancement commonly observed in low DMSO composition. This indicates the potential role of hydrophobic residues in helix-loophelix motif and the cluster in interfacial activation.